The Erotic Sentiment in Nāṭyaśāstra - Kumpiro, Pitchayawut (Journal of Letters, 2024)
Śṛṅgārarasa, the erotic sentiment, is the first and most significant of the eight sentiments in the sentiment theory in the Nāṭyaśāstra, the foremost treatise on Sanskrit drama, which also strongly influences the treatise on Sanskrit poetic writing, or the Alaṅkāraśāstra. As dramas ultimately aim to entertain readers and audiences, and the art of writing is one of the essential elements of creating dramas, a poet who thoroughly understands the theory of the bhāva (emotion) and rasa (sentiment) will firmly succeed in creating dramas. This article provides an in-depth explanation of the theory of the bhāva and rasa of Śṛṅgārarasa, covering their meaning, components, importance, relationship, and examples. The study indicates that the erotic in the Nāṭyaśāstra brings auspiciousness, happiness, and hope for life. It is the love of a woman and man that arises from beautiful natural environments and gentle treatment of each other in a loving relationship. There are two types of love in the Nāṭyaśāstra: successful and disappointed.